The Role of the Buddhist Sunday School Teacher in Building Children's Character - Eling Widiyono; Dika Arya Yasa (Edukasi, 2023)
This study aims to describe the process of forming children's character through the role of the teacher at the Buddhist Sunday School at Vipassana Kusalacitta Bekasi Temple. A qualitative descriptive approach was used in this study to gain a deep understanding of the experiences and perceptions of teachers and the learning processes involved. Character education has an important role in shaping and developing children's character in facing the challenges of the changing times. Teachers have a central role in creating an interesting learning environment, building good relationships with children, and using appropriate learning methods. In the context of Buddhist Sunday School or non-formal education, interesting learning is key in developing children's character. Methods such as stories, games, group discussions, and creative activities can be used by teachers to help children understand the concepts of characters that are taught in a fun and memorable way. This research is expected to provide insight to teachers in Buddhist Sunday Schools about effective ways to shape children's character and also provide recommendations for learning strategies in character education in Buddhist Sunday Schools or other non-formal education. With the joint efforts of teachers and appropriate learning methods, it is hoped that character education can be properly integrated into the education system to produce a generation that has integrity, cares for the environment, and is able to maintain peace and order in everyday life.